Arka Prakasha of Ravana: A Book Review (International Journal of Ayurveda and Pharma Research, 2022)
Arka prakasha is a text written by Ravana in the series of Sanskrit works by Ravana, the devotee of Lord Shiva. In this book there is extensive conversation between Ravana and his wife Mandodari. He explains each and every detail of the method of preparation of Arka (Distillate), the apparatus and different varieties of substance which is used for preparing Arka. He has explained everything in 10 chapters with each chapter containing 100 Shlokas in each chapter. Since each chapter contain 100 Shlokas, it is titled as Shataka. Arka is considered as one among the five basic principles (Pancha Vidha Kashaya Kalpana). The present work is an attempt to summarize the key feature of Arka Prakasha to highlight its utility and contribution in the development of Rasa Shastra and Bhaishajya Kalpana. And also, to study & summarize the important comprehensive and specific points mentioned in Arka prakasha. Thereby, to elaborate the contribution of Arka prakasha in the field of Rasashastra and Bhaishajya Kalpana.